A qualitative review of existing national and international occupational safety and health policies relating to occupational sedentary behaviour - Coenen, P.; Gilson, N.; Healy, G.; Dunstan, D.; Straker, Leon (Elsevier, 2017)
Prolonged sedentary time is now recognised as an emergent ergonomics issue. We aimed to review current occupational safety and health policies relevant to occupational sedentary behaviour. An electronic search for documents was conducted on websites of ergonomics and occupational safety and health organisations from 10 countries and six international/pan-European agencies. Additionally, 43 informants (nine countries) were contacted and an international conference workshop held. 119 documents (e.g. legislation, guidelines, codes of practice) were identified. Using a qualitative synthesis, it was observed that many jurisdictions had legal frameworks establishing a duty of care for employers, designers/manufacturers/suppliers and employees. While no occupational authority policies focusing specifically on sedentary behaviour were found, relevant aspects of existing policies were identified. We highlight implications for ergonomics research and practice and recommend the development of policy to specifically address occupational sedentary behaviour and support workplace initiatives to assess and control the risks of this emergent hazard.